Implementing Religious Moderation in Learning: Teachers' Steps to Foster Tolerance and Harmonization in a Multicultural School Environment - Al-Ulum, Muha Ruslan; Ali, Saidina; Zahid, Muhammad; Juharoh, Juharoh; Sahri, Sahri (The Magister of Islamic Education IAIN Pontianak, 2025)
This study aims to analyze the differences in religious identity among high school students based on gender in Sungai Banyak City. Religious identity is a crucial aspect in shaping students' character, encompassing dimensions of belief, religious practices, and moral values. The focus of this study is to describe how male and female students understand and practice religious values, as well as the factors influencing these differences. This research employs a quantitative approach with a random sampling technique. The sample consists of 1248 first-year high school students selected randomly from a population of 167 students. Data were collected through questionnaires distributed to the students. Data analysis was conducted using [statistical analysis method, eg, t-test, ANOVA, etc.] to evaluate gender differences in religiosity, as well as to test the statistical significance of the findings. The findings indicate that female students exhibit a higher level of religious identity compared to male students. This result reflects a greater involvement of females in religious practices, both in school and in community-based activities. However, this difference is statistically significant, with a p-value < 0.05, indicating that gender has a significant effect on students' religious identity. Social and cultural factors, such as gender roles in societal norms, play a significant role in shaping these differences. The implications of this study emphasize the need for a more inclusive approach in religious education to accommodate the needs of both male and female students in a balanced manner. Additionally, this study contributes to the development of a religious education curriculum that is relevant to local contexts and gender differences.